Up and down - up and down. How dynamic sitting and standing can improve health in the office (Dortmund, 2008)
"The aim of this brochure is literally to get you jumping to your feet. And not only while you're reading it, but several times a day. Why? Quite simply because we all spend too much time sitting. In our free time, at work, during training - modern man has neglected his talent for standing and has got used to the sitting position (at work as well). This has become possible thanks not least to computers and similar devices which have tied many people permanently to their desks. In former times it was still necessary to move around a bit in the office - fetching a file, taking some documents into the next office - but now all that's required for most jobs is a mouse click. This development makes things comfortable for us, but it doesn't do much for our health. In fact our whole organism needs movement to stay healthy in the long run. Something that is ignored in the daily routine of many people. And that's why around 8 % of those who work at the computer screen day after day suffer from a range of different health disorders, from sore eyes and tense shoulders through to back problems."